Selective inhibition of mitochondrial respiratory complexes controls the transition of microglia into a neurotoxic phenotype in situ - Chausse de Freitas, Bruno; Lewen, Andrea; Poschet, Gernot; Kann, Oliver (Brain, behavior and immunity, 2020)
Microglia are tissue resident macrophages (innate immunity) and universal sensors of alterations in CNS physiology. In response to pathogen or damage signals, microglia feature rapid activation and can acquire different phenotypes exerting neuroprotection or neurotoxicity. Although transcriptional aspects of microglial phenotypic transitions have been described, the underlying metabolic reprogramming is widely unknown. Employing postnatal organotypic hippocampal slice cultures, we describe that microglia transformed into a mild reactive phenotype by single TLR4 stimulation with lipopolysaccharide (LPS), which was boosted into a severe neurotoxic phenotype by IFN-γ (LPS + INF-γ). The two reactive phenotypes associated with reduction of microglial homeostatic “surveillance” markers, increase of cytokine release (IL-6, TNF-α) as well as enhancement of tissue energy demand and lactate production. These reactive phenotypes differed in the pattern of inhibition of the respiratory chain in mitochondria, however. TLR4 stimulation induced succinate dehydrogenase (complex II) inhibition by the metabolite itaconate. By contrast, TLR4 + IFN-γ receptor stimulation mainly resulted in complex IV inhibition by nitric oxide (NO) that also associated with severe oxidative stress, neuronal dysfunction and death. Notably, pharmacological depletion of microglia or treatment with itaconate resulted in effective neuroprotection reflected by well-preserved cytoarchitecture and electrical network activity, i.e., neuronal gamma oscillations (30-70 Hz) that underlie higher cognitive functions in vivo. Our findings provide in situ evidence that (i) proinflammatory microglia can substantially alter brain energy metabolism and (ii) fine-tuning of itaconate and NO metabolism determines microglial reactivity, impairment of neural network function and neurodegeneration. These data add mechanistic insights into microglial activation, with relevance to disorders featuring neuroinflammation and to drug discovery.